The Effect of Roselle Flower Infusion (Hibiscus sabdariffa) on Retinal Ganglion Cell Apoptosis of Sprague Dawley Rats Exposed to Cigarette Smoke - Riski Prihatningtias; Puspita Kusuma Dewi; Desy Armalina; Hermawan Istiadi; Rahma Athifah Amelia; Faizah Fulyani (Faculty of Medicine, Universitas Diponegoro, 2022)
Background: Cigarette smoke contains a lot of free radicals that can reduce antioxidants in the body. One of those is Reactive Oxygen Species (ROS) which can induce Retinal Ganglion Cell (RGC) apoptosis. Reduced ganglion cell axons will eventually lead to optic neuropathy. Supplementing herbal medicines, vitamins, foods, and drinks containing antioxidants is one way to increase oxidant levels in the body. Roselle or Hibiscus sabdariffa is a herbal plant reported to have a lot of antioxidant content.Objective: The study aimed to prove that Roselle flower infusions can reduce retinal ganglion cell apoptosis of Sprague Dawley rats exposed to cigarette smoke.Methods: This was an experimental study with a post-test-only design with a total of 24 male Sprague Dawley rats exposed to four non-filtered cigarettes/day for 30 consecutive days. They were randomly divided into four sub-groups, and each group consisted of 6 rats. The control group received 1 ml of saline, and three treatment groups received Roselle flower infusions of 2.5%, 5%, and 10% for 30 days. Enucleated eyes were then made paraffin blocks and slides with HE staining. The retinal ganglion cell apoptosis score was assessed by calculating the number of apoptotic cells using 1000x in five fields of view. The data were analyzed using Kruskal-Wallis non-parametric test followed by the Mann-Whitney U test.Results: The average retinal ganglion cell apoptosis score in control, treatment 1, 2, and 3 groups were 3.00; 2.83; 2.00; 1.83. There was a significant difference between the control group and treatment groups 2 (p=0.001) and group 3 (p=0.001), while between the control group and treatment group 1, there was no significant difference (p=0.317).Conclusion: The administration of 5% and 10% Roselle flower infusions can reduce the apoptosis score of retinal ganglion cells in Sprague Dawley rats exposed to cigarette smoke. The higher the Roselle flower infusion concentration, the lower the apoptosis score of retinal ganglion cells.